The idea of theater in open spaces (the city, the community) "Iraqi folk games as a model" (Journal of the College of Basic Education, 2023)
The problem stems from the question of difference and compatibility between the space of the idea of theater as a continuous process inOpen spaces and theatrical space as a production that has a beginning and an end.The first was linked to the production of the cultural policy of social control and balance between the individual and his physical environment.The second is the intellectual cohabitation of the manifestations of that relationship.Research importance:Indicates the importance of the idea of theater as a strategy and technique closely related to a person's private life.And social, closely related to the transformation and disclosure of human identity and renewal.Research goal:The political discourse draws attention to the technique and strategy of the idea of theater in the space of society.To develop and renew the human identity and its ability to integrate, produce, develop, invest and organizeResponsibility and control of the relationship between the individual and the institutions of society, regardless of the forced relationship orauthoritarianism.